2018
DOI: 10.1001/jamanetworkopen.2018.4154
|View full text |Cite
|
Sign up to set email alerts
|

Changes to Racial Disparities in Readmission Rates After Medicare’s Hospital Readmissions Reduction Program Within Safety-Net and Non–Safety-Net Hospitals

Abstract: This cohort study of Medicare data from 2007 to 2015 examines disparities in readmission rates between white and black patients discharged from safety-net or non–safety-net hospitals after initiation of the Hospital Readmissions Reduction Program (HRRP).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 37 publications
4
51
0
Order By: Relevance
“…For example, recent evidence has shown that racial disparities at safety-net hospitals for nonreported conditions have widened under HRRP. 18 Joynt Maddox and colleagues' findings also underscore the real consequences safety-net hospitals face as a result of treating socially vulnerable patients and are consistent with other recent analyses that attempt to account for social risk in readmission models using other social determinants of health. 19 To date, there is conflicting evidence about the extent to which HRRP reduces readmission rates 20 and recent concerns that it may harm care in other unintended ways, 21 though the final verdict is far from certain.…”
Section: In Their Study In This Issue Of Health Services Research Joyntsupporting
confidence: 79%
See 1 more Smart Citation
“…For example, recent evidence has shown that racial disparities at safety-net hospitals for nonreported conditions have widened under HRRP. 18 Joynt Maddox and colleagues' findings also underscore the real consequences safety-net hospitals face as a result of treating socially vulnerable patients and are consistent with other recent analyses that attempt to account for social risk in readmission models using other social determinants of health. 19 To date, there is conflicting evidence about the extent to which HRRP reduces readmission rates 20 and recent concerns that it may harm care in other unintended ways, 21 though the final verdict is far from certain.…”
Section: In Their Study In This Issue Of Health Services Research Joyntsupporting
confidence: 79%
“…They align with emerging research suggesting that current HRRP incentives may harm the capacity of safety‐net hospitals to do so. For example, recent evidence has shown that racial disparities at safety‐net hospitals for nonreported conditions have widened under HRRP . Joynt Maddox and colleagues’ findings also underscore the real consequences safety‐net hospitals face as a result of treating socially vulnerable patients and are consistent with other recent analyses that attempt to account for social risk in readmission models using other social determinants of health …”
supporting
confidence: 73%
“… 10 , 35 Nonetheless, because black patients frequently face greater challenges navigating discharge transitions, quality improvement interventions might have been more effective for black than white populations within the same hospitals. 21 …”
Section: Discussionmentioning
confidence: 99%
“…We also acknowledge that we did not explore the site of care where these patients received their surgeries given that previous investigators have shown that minority patients tend to receive care in low-quality, minorityserving hospitals. 26 Site of care is a critical variable that appears to mediate the pathway of the association of race with postoperative morbidity and mortality. 27 Unfortunately, the NSQIP-P program strongly discourages attempts to identify specific hospitals in the database.…”
Section: Figurementioning
confidence: 99%